ULTRASONOGRAPHIC OPTIC NERVE SHEATH DIAMETER MEASUREMENT FOR RAISED INTRACRANIAL PRESSURE IN A TERTIARY CARE CENTRE OF A DEVELOPING COUNTRY - Siddiqui, Naveed ur Rehman; Haque, Anwarul; Abbas, Qalab; Jurair, Humaira; Salam, Basit; Sayani, Raza (Journal of Ayub Medical College Abbottabad, 2018)
Background: Intracranial hypertension is not an uncommon life-threatening syndrome, caused by a variety of non-neurological and neurological illnesses, and quick diagnosis, timely treatment of Raised Intracranial Pressure (ICP) is associated with improved outcome. Our aim of study was to determine ultrasonographic measurement of Optic nerve sheath diameter (ONSD) for raised ICP. Methods: Prospective case series done in Emergency and Paediatric critical care unit of Aga Khan University Hospital. ONSD measurement in millimetres was done by placing linear probe of ultrasound on eye ball. Results: Forty-eight patients were included in study with mean age of 7.5±5.0 years with 21/48 (43.8%) between 1-8 years and 19/48 (39.6%) >8 years with 32/48 (66.7%) were male. Non-traumatic coma was most common diagnosis 41/48 (85.4%) with infectious cause being most common while Traumatic brain injury constitutes 7/48 (14.6%). Ct scan brain was done in 39/48 (81.3%) while MRI brain in rest of patients. Raised ICP was found in 83.33% (40/48) patients with Ultrasonographic ONSD measurement as compared to CT scan/MRI 14/48 (29.2%). 85% of patients, showed ultrasonographic ONSD measurement suggestive of Raised ICP with GCS ‰¤12. Mean ONSD with signs of raised ICP in infants 4.64 (±0.48), in 1-10 years 6.44 (±0.65), and in adolescent >10 years 6.28 (±0.62) ONSD respectively with ROC Curve showing Area Under Curve (AUC) 0.814 ( 95% CI, 0.692-0.936). Conclusion: We identified threshold of Ultrasonographic ONSD measurement in infants >4.0 mm, in children 1-10 yrs >4.71 mm, in adolescent >10 yrs >5.43 mm for raised ICP with sensitivity and specificity of 100% and 60-66.7% respectively. 85% of patients showed raised ICP with Ultrasonographic ONSD measurement with GCS ‰¤12. Keywords: Ultrasonography, Optic nerve sheath diameter, Raised Intracranial Pressure, Paediatric intensive care unit